Guidance on the risk assessment of food and feed from genetically modified animals and on animal health and welfare aspects - EFSA Panels on Genetically Modified Organisms (GMO) and Animal Health and Welfare (AHAW) (EFSA Journal)
Abstract This document provides guidance for the risk assessment of food and feed containing, consisting of or produced from genetically modified (GM) animals, as well as for the health and welfare assessment of these animals, within the framework of Regulation (EC) No 1829/2003 on GM food and feed. The assessment strategy seeks to deploy appropriate approaches to compare GM animals and derived food and feed with their respective comparators. The health status of a food/feed producing animal has traditionally been considered as an important indicator of the safety of derived foods/feed and therefore comparative analysis of the phenotypic characteristics of the GM animal with the traditionally‐bred animal, including health and physiological parameters, is considered an important component in the risk assessment. The document addresses the molecular characterisation, which provides information on the structure and expression of the insert(s) and on the stability of the intended trait(s); the toxicological assessment, which addresses the possible impact of biologically relevant change(s) in the GM animal and/or derived food and feed, the allergenicity assessment of the novel protein(s), as well as of the whole food derived from the GM animal; and the nutritional assessment to evaluate whether food and feed derived from a GM animal is as nutritious to humans and/or animals as food and feed derived from traditionally‐bred animals. This guidance document also addresses the scientific requirements for the assessment of health and welfare of GM animals bred for food and feed use. The assessment is made in terms of the effective functioning of their body systems in a given environment. The document does not cover the environmental risk assessment of GM animals, which will be addressed in stand‐alone guidance under development by the EFSA GMO Panel.